Key success factors for implementation of service-learning Malaysia University for Society (SULAM) projects at higher education level: community perspectives / Wan Nur Arina Dayana Mohd Naufal ... [et al.] - Mohd Naufal, Wan Nur Arina Dayana; Syed Aris, Sharipah Ruzaina; Wahi, Rafeah; Mohamed, Ani Mazlina Dewi; Zulkipli, Zulinda Ayu; Awang Hashim, Rosna; M Si, Elianawati; Mohd Yusof, Mohammad Mubarrak (Universiti Teknologi MARA, 2024)
The success of service-learning projects is often assessed based on students' learning outcomes, while less attention is given to understanding the key factors that contribute to these successes from the perspective of community partners. This paper addresses this knowledge gap by exploring those key factors, employing a collective case study approach with a qualitative design Three community partners involved in service-learning projects, or “SULAM” were interviewed to inquire about the success factors and strategies for sustaining community engagement and university collaboration. Data from this study was analysed thematically with three themes emerging: community needs, sustainable funding, and effective management. Discussions and personal connections between the university and community leaders are essential to understanding their needs and ensuring project relevancy and effectiveness. The role of the community leaders in guiding and mobilising the community, their interest, dedication, commitment and sustainable funding sources are essential factors to sustain SULAM projects. By gaining insights into the factors considered critical by the community, universities can make informed decisions to develop and implement more impactful and sustainable initiatives that prioritise community alongside students' learning outcomes.